Biological function of hpsh4590 localized in the plasticity zone of Helicobacter pylori. (April 2016) - Gu, Yu-feng; Li, Yu; Song, Yu; Chang, Xin; Qu, Ye-Min; Wang, Ming-Yi; Gao, Xiao-Zhong
Abstract: The aim of this study was to determine the biological function of hpsh4590 in Helicobacter pylori . After Hpsh4590 was expressed using a prokaryotic expression system, the cytotoxic effects and IL-8 production of Hpsh4590 were analyzed by co-culturing with GES-1 cells. Meanwhile, the antibody of rHpsh4590, produced by immunizing rabbit, was used for localization and protein interaction studies. Hpsh4590 fusion protein was expressed successfully in Escherichia coli Rosetta (DE3), and the polyclonal antibody was produced at high titers. The MTT assay showed that the inhibition ratio of GES-1 cells cultured with 0.1 μg/mL rHpsh4590 (3.02% ± 0.02%) was significantly lower than that of 20 μg/mL rHpsh4590 (57.57% ± 0.03%, p < 0.01 ), while DAPI staining showed the cytotoxic effects of rHpsh4590 for GES-1 cells. The up-regulation of cleaved caspase-3 and cleaved PARP was observed after GES-1 cells co-cultured with rHpsh4590 by Western blot. Co-culturing of GES-1 cells with rHpsh0459 (20 μg/mL) led to significant production of IL-8 at 12 h(1097.74 ± 212.37 pg/mL) and 24 h (1379.55 ± 209.58 pg/mL) then at 6 h(134.68 ± 14.64 pg/mL, p < 0.01). These observations suggest that the cytotoxicity of Hpsh4590 occurred in a concentration dependent manner, which is related with IL-8 secretion from gastric mucosal epithelial cells. Hpsh4590 was found localized in the membrane and the periplasm of H. pylori, interacted with zinc finger protein and methionine ABC transporter ATP-binding protein, and potentially regulates DNA uptake or transfer.